COLLECTIVE ACTIVITY OF PROFESSIONAL UNIONS IN SOCIAL STRUCTURE OF SOCIETY - Поліщук, О. С. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
Social-philosophic aspect of collective activity by way of example of professional unions is studied. The features are determined, and the role of language in collective activity of these social formations is revealed. It is proved that a person, as a bisocial creature, cannot exist outside labour unity. The dialogue as means of achievement intention is cleared up.